A rapid review of interventions to improve medicine self‐management for older people living at home - Giorgia Previdoli; V‐Lin Cheong; David Alldred; Justine Tomlinson; Savi Tyndale‐Biscoe; Jonathan Silcock; Daniel Okeowo; Beth Fylan (Wiley, 2023)
Abstract Background As people age, they are more likely to develop multiple long‐term conditions that require complicated medicine regimens. Safely self‐managing multiple medicines at home is challenging and how older people can be better supported to do so has not been fully explored. Aim This study aimed to identify interventions to improve medicine self‐management for older people living at home and the aspects of medicine self‐management that they address. Design A rapid review was undertaken of publications up to April 2022. Eight databases were searched. Inclusion criteria were as follows: interventions aimed at people 65 years of age or older and their informal carers, living at home. Interventions needed to include at least one component of medicine self‐management. Study protocols, conference papers, literature reviews and articles not in the English language were not included. The results from the review were reported through narrative synthesis, underpinned by the Resilient Healthcare theory. Results Database searches returned 14,353 results. One hundred and sixty‐seven articles were individually appraised (full‐text screening) and 33 were included in the review. The majority of interventions identified were educational. In most cases, they aimed to improve older people's adherence and increase their knowledge of medicines. Only very few interventions addressed potential issues with medicine supply. Only a minority of interventions specifically targeted older people with either polypharmacy, multimorbidities or frailty. Conclusion To date, the emphasis in supporting older people to manage their medicines has been on the ability to adhere to medicine regimens. Most interventions identify and target deficiencies within the patient, rather than preparing patients for problems inherent in the medicine management system. Medicine self‐management requires a much wider range of skills than taking medicines as prescribed. Interventions supporting older people to anticipate and respond to problems with their medicines may reduce the risk of harm associated with polypharmacy and may contribute to increased resilience in the system. Patient or Public Contribution A patient with lived experience of medicine self‐management in older age contributed towards shaping the research question as well as the inclusion and exclusion criteria for this review. She is also the coauthor of this article. A patient advisory group oversaw the study.